Effects of sample age and storage temperature on the flow cytometric diagnosis of chronic lymphocytic leukaemia in South Africa - Shaun M. Grobler; Anne-Cecilia van Marle (African Journal of Laboratory Medicine)
Background: Chronic lymphocytic leukaemia (CLL) is a haematological neoplasm with characteristic flow cytometric immunophenotyping. Pre-analytical variables impact the quality and reproducibility of flow cytometric data, which could alter the diagnosis from CLL to atypical CLL (aCLL).